Penyelesaian Sengketa Konsumen Melalui Pembentukan Badan Penyelesaian Sengketa Konsumen di Kota Jambi - Novalia Marbun; Pahlefi Pahlefi (Universitas Jambi, Fakultas Hukum, 2021)
The writing of this thesis examines the resolution of consumer disputes through the establishment of the Consumer Dispute Resolution Agency (BPSK) in the city of Jambi. The purpose of writing, knowing and analyzing consumer dispute resolution through BPSK so that it becomes urgent in the city of Jambi. Formulation of the problem regarding the form of consumer dispute resolution in the city of Jambi and the importance of non-litigation resolution, namely through BPSK so that it becomes urgent in the city of Jambi. The research method used is empirical research with descriptive qualitative analysis research specifications. The findings in this thesis, first of the twenty-two consumer complaints to the Indonesian Consumers Foundation (YLKI), ten cases of consumer disputes that entered the BPSK district / city of Bungo, five cases of consumer disputes that were submitted to the BPSK regency / city of Sarolangun. It appears that consumer complaint disputes will continue because the relationship between business actors and consumers is intertwined with one another. Second, the process of consumer dispute resolution assisted by YLKI is limited and does not have the final power as BPSK. Then, the government's attention is needed as an effort to improve the welfare of the community in helping people resolve consumer disputes by facilitating BPSK as a special body based on the mandate of consumer protection law. Abstrak Penulisan skripsi ini mengkaji mengenai penyelesaian sengketa konsumen melalui pembentukan Badan Penyelesaian Sengketa Konsumen (BPSK) di kota jambi. Tujuan penulisan, mengetahui dan menganalisis penyelesaian sengketa konsumen melalui BPSK sehingga menjadi urgen di kota jambi. Rumusan masalah mengenai bentuk penyelesaian sengketa konsumen di kota jambi dan pentingnya penyelesaian non litigasi yaitu melalui BPSK sehingga menjadi urgen di kota jambi. Metode penelitian yang digunakan penelitian empiris dengan spesifikasi penelitian deskriptif analisis kualitatif. Temuan dalam skripsi ini, pertama dari dua puluh dua pengaduan konsumen kepada Yayasan Lembaga Konsumen Indonesia (YLKI), sepuluh kasus sengketa konsumen yang masuk ke BPSK kabupaten/kota bungo, lima kasus sengketa konsumen yang masuk ke BPSK kabupaten/kota sarolangun. Terlihat bahwa sengketa pengaduan konsumen akan terus berlangsung karena hubungan antara pelaku usaha dan konsumen yang saling terikat satu sama lain. Kedua, adapun proses penyelesaian sengketa konsumen yang dibantu oleh YLKI terbatas dan tidak mempunyai kekuatan final seperti halnya BPSK. Kemudian, diperlukan perhatian dari pemerintah sebagai upaya mensejahterakan masyarakat dalam membantu masyarakat menyelesaikan sengketa konsumen dengan memfasilitasi BPSK sebagai badan khusus berdasarkan amanat undang – undang perlindungan konsumen.